A Novel Microlearning Asynchronous Curriculum to Improve Internal Medicine Trainees’ Confidence and Skill in Interpreting ECGs - Matthew Capustin; Spencer Weintraub; Ji-Cheng Hsieh; Jack Alboucai; Farzana Antara; Karen Friedman (Journal of Medical Education and Curricular Development)
Background Skills in electrocardiogram (ECG) interpretation are critical in clinical decision making but remain poor among Internal Medicine residents. There remains no standardized method for teaching ECG interpretation. Methods This study aimed to leverage the benefits of microlearning by assessing an asynchronous microlearning ECG curriculum for Internal Medicine residents at a single academic residency program between September 2023 and June 2024. The ECG curriculum was comprised of 30 mandatory weekly ECGs which included a clinical vignette, a 12-lead ECG, and a single multiple-choice or free response question posted on Microsoft Teams. Residents were required to submit interpretations within 1 week, after which the answer, a short description of ECG findings, and clinical pearls were posted. Data collection included pre-post surveys with a 1- to 5-Likert scale measuring self-reported confidence and a test containing 15 unique ECGs. Results Of 151 total categorical and preliminary Internal Medicine residents, 38 (25.2%) completed pre-post surveys and were analyzed as matched pairs. Residents demonstrated increases in Likert ratings of confidence (mean post-pre score difference 0.44 of 5, P  = <.01), overall performance (mean post-pre raw score difference 0.97 of 15, P  = <.01), and performance in identifying normal variants (mean post-pre score subset difference 14.21%, P  = .017). Residents had no significant change in performance in identifying tachyarrhythmias (mean post-pre score subset difference 5.9%, P  = .24), ST-segment changes (0.88%, P  = 0.89), or conduction disease (−0.65%, P  = .92). Conclusions Overall, this curriculum was effective in improving resident confidence in and knowledge of ECG interpretation, with a particular strength in identifying normal/normal variants. Next steps include targeting specific ECG pathologies in which residents show particular knowledge gaps and creation of a 3-year longitudinal curriculum to reinforce knowledge over the course of a 3-year residency.